Los elementos del costo, identificación y aplicación para la cuantificación de los servicios de transporte particular de personas - VillegasFlores, Joselina Yomaira (2015)
There’s been a research about the companies transportation services of people with strong will and growth in the province of El Oro; that committee employees to take action according to their understanding of their economic activities. In which shows that have not been beneficial and easy so the plan of this research has been in charged tp help design a system of cot of production “Cap. Luis Lambert Orellana”, this cooperative will not have enough evidence to support the minimum cost of USD$1,50. In conclution, we have found a solution to take action of this test, involves a system of absorbing cost that with be founded. This procedure will be abed to all the cost of services that will be collaborating in the production of becoming the price of the service and the research for the most important products of this activity that will also operates the vehicles and demonstrates the least cost imposed by the authorities whether if it covers the operating cost.